Training of Super Users Contributes to Productivity in Molecular Biology Laboratories in Mozambique. (11th September 2019) - Assane, Mariamo; Basu, Debby; Landgraft, Kenneth; Pinto, Isabel; Adamo, Noorbebi; Macave, Admiro; Nhabomba, Augusto; Benzane, Octavia
Abstract: HIV viral suppression through antiretroviral (ARV) treatment has public health benefits in potentially reducing the risk of subsequent HIV transmissions. Mozambique has adopted the World Health Organization (WHO) "Test and Start" strategy, which assumes that all people who test positive for HIV start ARV treatment immediately. In order that treatment is guided by the respective HIV viral load (VL) test results, the MOH expanded the network of VL testing laboratories. About 26 VL testing instruments are now operational in the country. Although the increase in testing platforms increased VL tests performed, problems associated with errors, failures in user maintenance, and equipment malfunctions occur frequently. Delays in resolving equipment malfunctions contributed to lower laboratory productivity in certain periods of 2018. Therefore, the MOH, in coordination with the American Society for Clinical Pathology (ASCP) and VL testing instrument manufacturers, provided targeted training for VL laboratory Super Users (SUs). The SUs are primarily composed of laboratory technicians representing all VL laboratories. Training focused on equipment maintenance, software configuration, and troubleshooting the most common instrument-related problems and errors. Following this training, the SUs worked as in-laboratory equipment supervisors, helping laboratory staff to better perform equipment maintenance procedures. Furthermore, they worked remotely with representatives and field technicians of the instrument manufacturers to resolve small problems, such as accessory replacement and adding new users to the systems, in their own laboratories. This has led to a reduction in the overall time to equipment repair, less reliance on external field technicians, and correspondingly increased overall lab productivity and workforce capacity building for VL laboratory SU.